Competitiveness and the Gender Gap among Young Business Professionals - Ernesto Reuben; Paola Sapienza; Luigi Zingales (Institute for the Study of Labor (IZA), 2015)
Important gender differences in earnings and career trajectories persist. Particularly, in professions such as business. Gender differences in competitiveness have been proposed as a potential explanation. Using an incentivized measure of competitiveness, this paper investigates whether competitiveness explains future gender differences in earnings and industry choice in a sample of high-ability MBA graduates. We find that competitive individuals earn 9% more than their less competitive counterparts do. Moreover, gender differences in competitiveness explain around 10% of the overall gender gap. We also find that competitive individuals are more likely to work in high-paying industries nine years later, which suggests that the relation between competitiveness and earnings persists in the long run. Lastly, we find that the competitiveness gap in industry emerges over time when MBAs and firms interact with each other.
Keywords: J16; D81; D84; I21; C93; 330; gender gap; gender differences; competitiveness; business career